Strategic management essentials: tools, techniques, and best practices - Pasahol, Jhon Ven Saint L.; Gapasin, Willy O. (Manila Mindshapers Co., Inc., 2024)
A comprehensive overview of strategic management concepts, frameworks, and real-world applications. Covering topics such as external and internal analysis, business and corporate strategies, international expansion, innovation, corporate governance, and emerging trends, the book equips readers with essential tools like SWOT analysis, Porter$1 (Bs Five Forces, the Balanced Scorecard, and strategic matrices. It also includes case studies of major companies, offering practical insights into effective strategy formulation and execution.s
Includes bibliographical references.
Keywords: Strategic Management